Recommendations for the development of augmented reality video games for children with ADHD - Castañeda, Augusto Morante (2024)
Currently, the percentage of children with Attention-Deficit/Hyperactivity Disorder (ADHD) is between 7% in Peru. This is a problem for their development at an early age, since they would demonstrate poor academic performance compared to neurotypical children. This paper aim is to propose 10 recommendations to develop a video game with Augmented Reality for children with ADHD. The recommendations have been extracted from 25 research works. Specifically, the proposal is based on the extraction of recommendations for development video games with Augmented Reality for children with ADHD. The recommendations were divided into 2 categories: (i) Video game development recommendations with augmented reality, (ii) Video game components recommendations. For a better understanding, an illustrative example was developed with the use of the proposed recommendations. This work may be of interest to video game developers focused on children with ADHD.